ANALISIS FAKTOR INTERNAL PERUSAHAAN DAN AGENCY COST TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN RITEL - Erna Apriani (LP2M Universitas Bina Bangsa, 2022)
This study aims to examine the effect of financial ratios of profitability, liquidity, leverage and agency costs on financial distress. The financial ratios tested are profitability, liquidity, leverage, and agency cost ratios. This type of research is casuality research and the data used is secondary data, the population of this study is retail companies listed on the IDX for the 2018-2020 period, the sampling technique was carried out with purposive sampling techniques, based on the criteria obtained a sample of 13 companies, the data analysis used in this study used binary logistic regression. Based on the results of the research conducted, it shows the results of the profitability ratio of the liquidity ratio, the leverage ratio which has no effect on the possibility of financial distress, and agenct costs affecting the positive direction of the possibility of financial distress. Limitations in this study. First, the study was conducted only on retail companies. Second, this study only focuses on financial factors that can affect financial distress. Third, the research period is only from 2018-2020. These four studies are only focused on research variables. This research contribution can be used as a reference for companies or individuals to analyze the possibility of financial distress, and for academics it can be used as a repression for continuous research